2022
DOI: 10.3389/fmicb.2022.840825
|View full text |Cite
|
Sign up to set email alerts
|

The Serious Challenge of Occult Hepatitis B Virus Infection-Related Hepatocellular Carcinoma in China

Abstract: BackgroundIt is unknown how many people in China have chronic occult hepatitis B virus (HBV) infection (OBI) [chronic HBV infection with negative serum hepatitis B surface antigen (HBsAg) (N-HBsAg)]. Their clinical and virological characteristics, especially the correlation between the OBI and hepatocellular carcinoma (HCC), are still elusive and need to be investigated, including prevention, early diagnosis, and treatment strategies.Methods138 patients with HCC related to OBI were screened from 698 patients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Nearly two-thirds of OBI patients have varying degrees of liver fibrosis. A small number of OBI patients have an abnormal liver function and liver disease-related symptoms, indicating that OBI is not in a “healthy state.” From 12 to 36 weeks of observation, serum hepatitis B surface antigen and HBV DNA reactivation were found in two patients of Group B, which meant that HBV in the OBI state is not always stable or cleared, consistent with our previous findings ( 11 , 13 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Nearly two-thirds of OBI patients have varying degrees of liver fibrosis. A small number of OBI patients have an abnormal liver function and liver disease-related symptoms, indicating that OBI is not in a “healthy state.” From 12 to 36 weeks of observation, serum hepatitis B surface antigen and HBV DNA reactivation were found in two patients of Group B, which meant that HBV in the OBI state is not always stable or cleared, consistent with our previous findings ( 11 , 13 ).…”
Section: Discussionsupporting
confidence: 91%
“…also found that serum anti-HBs titers were inversely proportional to the risk of HBV reactivation following re-positivity of the surface antigen ( 20 ). In a previous study of OBI patients, our team discovered that the average diameter of HCC in anti-HBs-positive patients was significantly smaller than that in anti-HBs-negative patients ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations